Sistem pangan lokal: Konsep, prospek, dan contoh sukses - Siahaan, Tito Summa (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: This article aims to explore several key concepts of local food systems and examine some examples of policies adopted in several countries. Methods: The discussion is based on a literature review related to the phenomenon under study. Finding: The Indonesian government is committed to achieving the sustainability goals outlined in the Sustainable Development Goals (SDGs), where ending hunger by 2030 is goal number 2. In achieving this SDG goal number 2, and in the context of overall food security, geographical conditions pose a major challenge that must be addressed. Currently, the developed food system tends to be centralized and industrialized, which has been fairly effective so far as shown by several indicators. However, there are still some food insecure areas in Indonesia. For these food insecure areas, the author argues that there needs to be a shift away from a centralized and industrialized approach. The development of local food systems can be one solution with the direction to serve as a complementary function to centralized food systems. Policy replication alone will not be sufficient. Conclusion: Therefore, there needs to be an understanding of local-specific characteristics to build appropriate policy models. Novelty/Originality of this article: This article provides important recommendations on the significance of local food systems for regions that are remote from central areas.